Reform and Religious Heterodoxy in Thomas Robert Malthus’s “Crises” and the First Edition of the Essay on the Principle of Population - Stewart, John (Circumscribere International Journal for the History of Science, 2017)
The first edition of Thomas Robert Malthus’ Essay on the Principle of Population is best understood as an exploration of human nature and the role of necessity in shaping the individual and society. The author’s liberal education, both from his father and his tutors at Warrington and Cambridge, is evident in his heterodox views on hell, his Lockean conceptualization of the mind, and his Foxite Whig politics. Malthus’ unpublished essay, “Crises,” his sermons, and the the last two chapters of the Essay (which were excised from subsequent editions) reveal a pragmatic, compassionate side of the young author that was under appreciated by both his contemporary critics and modern historians. The Essay has been mischaracterized by David McNally (2000) as a “Whig response to Radicalism” and by Patricia James (1979) as a reaction by Malthus against his father’s liberalism. This article argues that when he wrote the first edition of the Essay on the Principle of Population, Malthus was himself a liberal dissenter and Foxite Whig rather than an orthodox Anglican or a Burkean defender of traditional class relations.